Evaluation of the Clinical Performance of NuSmile Pedodontics Zirconia Crowns in Pulp-Treated Primary Teeth—2 Years Follow-Up Study - Alamoudi, Rana A.; Walia, Tarun; Debaybo, Dina (European Journal of Dentistry, 2022)
Objectives There is a lack of information regarding the longevity of prefabricated crowns on primary teeth. Therefore, the objective of the present study was to evaluate the clinical success rate of NuSmile pediatric Zirconia crowns in both primary anterior and posterior teeth up to 2 years in terms of gingival health, levels of plaque, restoration failure, and marginal integrity.Materials and Methods This interventional study evaluated the clinical performance of NuSmile primary Zirconia crowns on 232 (172 primary incisors and 60 primary molars) pulp-treated primary teeth. Statistical analysis included independent t-test and Kaplan–Meier survival method for which the level of significance was set up at p < 0.05.Results Gingival and plaque index of the teeth restored with NuSmile Zirconia crowns (test tooth) compared with adjacent and antagonist teeth (control tooth) showed no statistically significant difference at all time intervals (p > 0.05). The Kaplan–Meier survival graph indicated that only 34% of NuSmile Zirconia incisor crowns and 86% of NuSmile Zirconia molar crowns have survived at the end of 24 months. Of the 172 NuSmile Zirconia incisor crowns placed, only 82 teeth survived at the end of 2 years and the majority of the crowns completely lost the Zirconia crown. The Kaplan–Meier graph also indicated that more than two-thirds of crowns, i.e., 90% incisor crowns and 76% of molar crowns, had good marginal integrity at the end of 24 months.Conclusions Zirconia pediatric crowns preserve and maintain gingival health and have long-term survival rates with good retention and marginal integrity, indirectly preventing secondary caries. Hence, Zirconia pediatric crowns are a well-suited restoration of choice for primary teeth rehabilitation.
Keywords: Zirconia pediatric crowns; NuSmile; clinical success; primary teeth; incisors; molars